2006
DOI: 10.1111/j.1365-2257.2006.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated separation of cord blood units in top and bottom bags using the Compomat G4

Abstract: Cord blood (CB) has become a real alternative source of haematopoietic stem cells for bone marrow reconstitution in a variety of malignant disorders. As a response to this increasing activity, CB banks have been developed to guarantee the quality of processed CB units. Volume reduction of CB units maximizes storage space and also has other advantages. The aim of this study was to develop a program for the volume reduction of CB in the Compomat G4 device. We also compared two different top and bottom systems fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The positive findings of that study showed that cord blood units could be processed routinely with that method, with high TNC recovery. In another study of 2006, Solves and collaborators 13 developed a program for the separation of centrifuged cord blood into components and compared it with two top‐and‐bottom techniques (Compomat G4 and Optipress II). Volume reduction with the Compomat G4 allowed acceptable cell recoveries if the volume was reduced to 41 mL (79.7 and 76.2% for the units with an initial volume less than or more than 100 mL) but not very good cellular yields (68%) if the volume was reduced to 25 mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive findings of that study showed that cord blood units could be processed routinely with that method, with high TNC recovery. In another study of 2006, Solves and collaborators 13 developed a program for the separation of centrifuged cord blood into components and compared it with two top‐and‐bottom techniques (Compomat G4 and Optipress II). Volume reduction with the Compomat G4 allowed acceptable cell recoveries if the volume was reduced to 41 mL (79.7 and 76.2% for the units with an initial volume less than or more than 100 mL) but not very good cellular yields (68%) if the volume was reduced to 25 mL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be noted that such procedures reduce not only expensive cryogenic space needs, but also unnecessary components of stem cells transplants—red blood cells (RBCs), plasma, dimethyl sulfoxide (DMSO)—which can cause untoward reactions in recipients 2 . Although many published procedures of cord blood volume reduction report small losses of hematopoietic progenitor cells, 3‐14 we are unaware of studies showing the stability of high‐quality parameters during many years of routine monitoring. Therefore, we present in this report the analysis of a quality control (QC) program carried out at the Milano Cord Blood Bank from 1998 to 2007.…”
mentioning
confidence: 99%
“…To date, these systems are widely used to extract a fraction of TNCs out of CB [10][11][12][13]. Their effectiveness was evaluated in the framework of technological solutions of semi-automatic separation systems [14], and in comparison with other CB processing methods [15,16]. Experience shows clear perspectives of semi-automatic systems [17] to satisfy high and stable CB cells yield.…”
Section: Isolation Of Nucleated Cells Fraction From Umbilical Cord Blood -Choice Of Methodsmentioning
confidence: 99%
“…The cord blood units collected in triple bag system were centrifuged in oval buckets at 3,000 g for 12 min at 22 ° C, ensuring that the bags were well supported to prevent disruption of the buffy coat layer. UCB collections were separated into plasma, red blood cell concentrate and buffy coat containing haematopoietic progenitors in different devices (Optipress II and Compomat G4), as previously reported [12] . Before processing cord blood units, volume was calculated and samples were drawn for cell counts.…”
Section: Red Cell Depletionmentioning
confidence: 99%